2021
DOI: 10.3390/curroncol28050321
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA 5hmC and CK195hmC+ Contents: A Promising Biomarker for Predicting Prognosis in Small Hepatocellular Carcinoma

Abstract: Background: 5-Hydroxymethylcytosine (5hmC) with dynamic existence possesses multiple regulatory functions. Whereas, 5hmC’s impact on small hepatocellular carcinoma (SHCC) remains unclear. The present work focused on characterizing 5hmC content within SHCC and assessing the possibility of using global genomic 5hmC level as the predicative factor of clinical outcome. Methods: This study applied ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) in measuring 5mC, 5fC and 5hmC cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This results in a chemical modification where methyl groups are covalently bonded to the cytosine residues [ 37 ]. Different types of DNA methylation include 5-methylcytosine (5mC), 5-hydroxymethylcytosine (5hmC), N6-methyladenine and others [ 38 , 39 ], with 5mC being the most common type, and its DNA methylation status is influenced by specific regulatory molecules.…”
Section: Methylation Mechanism and Functionmentioning
confidence: 99%
“…This results in a chemical modification where methyl groups are covalently bonded to the cytosine residues [ 37 ]. Different types of DNA methylation include 5-methylcytosine (5mC), 5-hydroxymethylcytosine (5hmC), N6-methyladenine and others [ 38 , 39 ], with 5mC being the most common type, and its DNA methylation status is influenced by specific regulatory molecules.…”
Section: Methylation Mechanism and Functionmentioning
confidence: 99%
“…The antibody was previously validated for use in IHC and in thyroid carcinoma. [15][16][17] 5hmC IHC (Clone 4D9) Following de-paraffinization and rehydration of FFPE sections, heat-induced antigen retrieval was performed using a decloaking chamber (Biocare Medical, Pleasant Hill, CA) set for 5 min at 110C in citrate buffer pH 6 (article C-9999, Sigma-Aldrich, St. Louis, MO). For quenching of endogenous peroxidase, a 30-min incubation in 0.15% hydrogen peroxidase was performed at room temperature, followed by a 30-min blocking step using 1% bovine serum albumin (article A-4503, Sigma-Aldrich, MA).…”
Section: Mhc Ihc (Clone Rm236)mentioning
confidence: 99%
“…When we looked at the physiological functions of the TET proteins and their mechanisms of regulation of DNA methylation and transcription, out of the three TET genes TET1 and TET2, expression levels were shown to be low in hepatocellular carcinoma (HCC) tissues [ 303 , 304 ]. Studies have also revealed that global genomic 5hmC levels are down-regulated in HCC tissues and cell lines [ 305 , 306 ]. For designing early detection and therapeutic strategies, 5hmC signatures found in HCC tissues and in circulating cell-free DNA are important [ 305 ].…”
Section: Epigenetic Tumor Heterogeneity and Sequencing Technologiesmentioning
confidence: 99%